Male Protagonist’s Realization the Value of Life in His Afterlife in Mitch Albom’s Novel “For One More Day”: การตระหนักรู้คุณค่าของชีวิตในโลกหลังความตายของตัวละครเอกชายในนวนิยายเรื่อง ขอเพียงอีกวัน (For One More Day) - Manhadee, Kanyaruk (JOURNAL OF LANGUAGE, RELIGION AND CULTURE, 2022)
This article examines the novel For One More Day, 2006, written by Mitch Albom, in terms of analyzing the mental problems of the male protagonist. This is due to a patriarchal society in which male success is transmitted through family institutions. The solution was found in a spiritual way that emphasized the value of women in tenderness. Empathy for others can help alleviate the male protagonist's desire to commit suicide. The text presents that patriarchal power is passed through the father. A father clinging to material success results in his son having mental problems when he is unable to maintain success and fame, so he desires to commit suicide. The author, therefore, presents the protagonist on a near-death journey. This area presents the limitation of the worldview that values external objects and assets. And offer a solution by changing the perspective of life. The protagonist revisits the problems and sees the value of life in finding a balance between work and life in a spiritual way. Through a near-death experience and returning to the real world, the protagonist is able to go on with his life and changed his mind not to commit suicide.